Dwa aspekty komunikacji. Założenia komunikologii historycznej - Kulczycki, Emanuel (Wydawnictwo Naukowe UAM, 2015)
In this book, I demonstrate the conditions under which we can examine the past communication phenomena. Therefore, it consists of considerations within the scope of the methodology of humanities and philosophy of communication. This means that the subject of my research is both communication itself as well as how it is analyzed. I write about two aspects of “the same” communication, i.e., about the media and about our collective representations. So, I describe how it is possible to write the history of ways of thinking about communication. My analysis results in a catalogue of assumptions, i.e. philosophical conditions for communication history.
Książka udostępniona jest na licencji Creative Commons Uznanie autorstwa 4.0 Międzynarodowe (https://creativecommons.org/licenses/by/4.0/deed.pl).
Keywords: Communication; Philosophy of communication; Communication history; Methodology of humanities; Collective representations; Media